Socio-demographic predictors of overweight and obesity among adults in Ekpoma, Nigeria - Ogechi, Nmorsi Patience; Ismail, Suriani; Abdul Manaf, Rosliza; Oyibo, P. G. (Community Health Society Malaysia, 2018)
Background: Being overweight and obese are major causes of weight related health risks which are linked to morbidity and mortality. It is also rated as the sixth most essential threat in terms of number of deaths in the world and a major public health challenge globally. While this epidemic is prominent among developed countries, the prevalence is also increasing in developing countries such as Nigeria. The objective of this study is to determine the prevalence of overweight and obesity among adults in Ekpoma, Nigeria and also its socio-demographic predictors. Materials and Method: A cross sectional study was conducted in 2017 among adults in Ekpoma, Nigeria. The inclusion criteria included adults aged between 18 – 65 years. Data was collected using a pretested self-administered questionnaire and analysed using IBM SPSS version 22. Respondents’ body mass index (BMI) was categorised into 2 categories namely ‘overweight and obese’ and ‘not overweight and obese’. Chi square, simple and multiple logistic regressions were used to determine socio-demographic associations and predictors of ‘overweight and obesity’ among the respondents. Results: A total of 445 respondents were recruited. Most respondents’ were aged between 18-44 years (69.2%), female (51.2%), single (50.8%) and from the Edo ethnic group (72.1%), with 60.7% of them found to be ‘overweight and obese’. There were statistically significant associations between ‘overweight and obese’ with age (p = 0.001), gender (p = 0.033), marital status (p = 0.001) and ethnicity (p = 0.008). However the significant predictor for ‘overweight and obese’ was only marital status (AOR = 0.238, 95% CI = 0.143-0.398). Conclusion: The findings in this study showed that there is a high prevalence of overweight and obesity among adults in Ekpoma, Nigeria, and it is significantly associated with age, gender, marital status, and ethnicity, but only marital status is a significant predictor.